Qishen granules regulate intestinal microecology to improve cardiac function in rats with heart failure - Gao, Kuo; Yu, Xue; Li, Fanghe; Huang, Yiran; Liu, Jiali; Liu, Siqi; Lu, Linghui; Yang, Ran; Wang, Chao (Frontiers in Microbiology, 2023)
Abstract Introduction: Qishen Granule (QSG), a clinically approved traditional Chinese medicine, has been researched for treating heart failure (HF) for many years, However, the effect of QSG on intestinal microecology remains unconfirmed. Therefore, this study was aimed to elucidate the possible mechanism of QSG regulating HF in rats based on intestinal microecological changes. Methods: The rat model with HF induced by myocardial infraction was prepared by left coronary artery ligation. Cardiac functions were assessed by echocardiography, pathological changes of heart and ileum by Hematoxylin–eosin (HE) and Masson staining, mitochondrial ultrastructure by transmission electron microscope, and gut microbiota by the 16S rRNA sequencing. Results: QSG administration improved cardiac function, tightened cardiomyocytes alignment, decreased fibrous tissue and collagen deposition, and reduced inflammatory cell infiltration. Electron microscopic observation of mitochondria revealed that QSG could arrange mitochondria neatly, reduce swelling and improve the structural integrity of the crest. Firmicutes was the dominant composition in the model group, and QSG could significantly increase the abundance of Bacteroidetes and Prevotellaceae_NK3B31_group. Furthermore, QSG significantly reduced plasma lipopolysaccharide (LPS), improved intestinal structure, and recovered barrier protection function in rats with HF. Conclusion: These results demonstrated that QSG was able to improve cardiac function by regulating intestinal microecology in rats with HF, suggesting promising therapeutic targets for HF.